Cytokine screening identifies TNF to potentially enhance immunogenicity of pediatric sarcomas - Hendrik Gassmann; Hendrik Gassmann; Melanie Thiede; Jennifer Weiß; Emilie Biele; Luisa Flohé; Helena Lachermaier; Carolin Prexler; Valentina Evdokimova; Laszlo Radvanyi; Irfan Akhtar; Mina N. F. Morcos; et al. (Frontiers in Immunology)
IntroductionPediatric sarcomas, including osteosarcoma (OS), Ewing sarcoma (EwS) and rhabdomyosarcoma (RMS) carry low somatic mutational burden and low MHC-I expression, posing a challenge for T cell therapies. Our previous study showed that mediators of monocyte maturation sensitized the EwS cell line A673 to lysis by HLA-A*02:01/CHM1319-specific allorestricted T cell receptor (TCR) transgenic CD8+ T cells (CHM1319 CD8+ T cells).MethodsIn this study, we tested a panel of monocyte maturation cytokines for their ability to upregulate immunogenic cell surface markers on OS, EwS and RMS cell lines, using flow cytometry. xCELLigence, SRB and ELISpot assays were used to assess whether TNF pretreatment increases CD8+ T cell cytotoxicity.ResultsWe observed that TNF and IL-1β upregulated MHC class I, ICAM-1 as well as CD83 and PD-L1 on the surface of pediatric sarcoma cell lines, while IL-4, GM-CSF, IL-6 and PGE2 failed to induce respective effects. Although pretreatment of pediatric sarcoma cell lines with TNF did not improve unspecific peripheral blood mononuclear cells (PBMCs) cytotoxicity, TNF enhanced specific lysis of 1/3 HLA-A2+ EwS cell lines by CHM1319 CD8+ T cells depending on MHC-I expression and ICAM-1 upregulation.DiscussionOur study supports utilization of TNF or TNF-inducing regimens for upregulation of MHC-I and costimulatory surface molecules on pediatric sarcoma cells and for enhancing recognition of responsive HLA-A2+ EwS tumor cells by antigen-specific CD8+ T cells.